2012
DOI: 10.1063/1.3694044
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency droop in AlGaInP and GaInN light-emitting diodes

Abstract: At room temperature, AlGaInP pn-junction light-emitting diodes (LEDs) emitting at 630 nm do not exhibit an efficiency droop. However, upon cooling the AlGaInP LEDs to cryogenic temperatures, they show a pronounced efficiency droop. We attribute the efficiency droop in AlGaInP LEDs to electron-drift-induced reduction in injection efficiency (i.e., carrier leakage out of the active region) mediated by the asymmetry of the pn junction, specifically the disparity between electron and hole concentrations and mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 18 publications
5
44
0
Order By: Relevance
“…The green LEDs that have lower p p0 , µ p , and a higher δ value than the blue LEDs' counterparts should have not only a larger C DL , but also a lower J Onset-of-droop , according to Equations (1) and (2). The onset of the efficiency droop is observed at current densities of 2.96 A/cm 2 for the blue LED and 0.33 A/cm 2 for the green LED, consistent with our expectation, and with results reported in the technical literature [26][27][28][29]. It is worthwhile to note that the green LEDs typically have a higher SRH non-radiative recombination coefficient A SRH than the blue LEDs, because of more defect sites in the epitaxial films caused by the larger lattice mismatch between the GaInN well and GaN barrier [30].…”
Section: Resultssupporting
confidence: 81%
“…The green LEDs that have lower p p0 , µ p , and a higher δ value than the blue LEDs' counterparts should have not only a larger C DL , but also a lower J Onset-of-droop , according to Equations (1) and (2). The onset of the efficiency droop is observed at current densities of 2.96 A/cm 2 for the blue LED and 0.33 A/cm 2 for the green LED, consistent with our expectation, and with results reported in the technical literature [26][27][28][29]. It is worthwhile to note that the green LEDs typically have a higher SRH non-radiative recombination coefficient A SRH than the blue LEDs, because of more defect sites in the epitaxial films caused by the larger lattice mismatch between the GaInN well and GaN barrier [30].…”
Section: Resultssupporting
confidence: 81%
“…In a recent publication, Shim et al also suggested the possibility of a current dependent shift of the mean position of recombination for InGaAlPLEDs under electric current. 13 In our case, we treat the case of optical excitation of an InGaAlP-LED structure. Figure 6 shows the simulated inhomogeneous distribution of the radiative recombination rate for varying bias under constant laser excitation and for varying laser intensity under constant bias, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetric shapes and the slope variation of the short-wavelength edge of the emission spectrum with current shown in Fig.2a, can be attributed to increasing junction temperature 13 . To further investigate into behaviour of the peak wavelength and spectral width, the EL intensity evolution during the microsecond current pulses was monitored via photodiode response under the same operating conditions, as shown in Fig.2d.…”
Section: Spectral Behaviourmentioning
confidence: 95%
“…At low current densities, carrier leakage due to asymmetric p-n junction has been suggested to contribute towards efficiency decrease in AlGaInP LEDs 12,13 . Comprehensive studies of internal quantum efficiency (IQE) of amber/red AlGaInP LEDs 14,15 have attributed the leakage to insufficiently high barriers separating quantum wells (QWs) in the LED active regions.…”
Section: Introductionmentioning
confidence: 99%